2021
DOI: 10.14202/vetworld.2021.120-128
|View full text |Cite
|
Sign up to set email alerts
|

Novel in vitro and in vivo anti-Helicobacter pylori effects of pomegranate peel ethanol extract

Abstract: Background and Aim: Interest in plants with antimicrobial properties has been revived due to emerging problems associated with using antibiotics to eradicate Helicobacter pylori. Accordingly, this study aims to assess the antibacterial effects of Punica granatum and the possible synergistic effect of its extract along with metronidazole against H. pylori. Materials and Methods: Pomegranate peel ethanol extracts (PPEE) was tested against a control strain of H. pylori (NCTC 11916) in vitro and in vivo in female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In this study, the PRE/Zn (II) combination exerted potentiated activity in reducing colonization and inhibiting growth control. The anti-adhesive activity of PRE has been confirmed in the literature [77,78]. PRE's activity on biofilm formation, inhibition and eradication could support the potential efficacy of PRE and the PRE/Zn (II) combination as a preventive agent in catheter-related infectious diseases caused by M. luteus, e.g., as a coating on the catheter surface prior to use.…”
Section: Discussionmentioning
confidence: 68%
“…In this study, the PRE/Zn (II) combination exerted potentiated activity in reducing colonization and inhibiting growth control. The anti-adhesive activity of PRE has been confirmed in the literature [77,78]. PRE's activity on biofilm formation, inhibition and eradication could support the potential efficacy of PRE and the PRE/Zn (II) combination as a preventive agent in catheter-related infectious diseases caused by M. luteus, e.g., as a coating on the catheter surface prior to use.…”
Section: Discussionmentioning
confidence: 68%
“…Also, it was mentioned that P. granatum peel extracts revealed higher biological properties than extracts obtained from several other parts of pomegranate (except that of flower) (Fischer et al., 2011). Interestingly, a recent study reported that ethanol pomegranate peel extract of Jordanian origin was well established to reduce Helicobacter pylori infection (Mayyas et al., 2021). However, there are no studies regarding the chemical composition and antioxidant activity of pomegranate peel in Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…The MIC of each plant extract and clindamycin were determined using a microdilution method (Mayyas et al 2021). All tests were done in triplicate using 96-well microplates.…”
Section: Determination Of Micmentioning
confidence: 99%